Penerapan Model Pembelajaran Kooperatif pada Matakuliah Bimbingan Konseling Untuk Meningkatkan Prestasi Belajar Mahasiswa PGSD Semester 1 STKIP PGRI Bangkalan - Ernawati, Ernawati (Penerbit STKIP PGRI Bangkalan, 2018)
Abstract The purpose of this study is to improve the learning achievement of guidance counseling course by applying the model of cooperative learning media on pgsd students semester 1 stkip pgri bangkalan academic year 2017/2018. The type of this research is qualitative research which aims to know the application of cooperative learning model to student achievement of pgsd semester 1. This research uses population approach, so from the total population as much as 20 students are taken to be observed. Methods of data analysis Calculate student activity data and calculate student responses in learning. The use of cooperative learning media model on the students of semester 1 stkip pgri bangkalan, proved to improve student achievement, with the value of learning quality 3.00 Good learning quality criteria, which before the value of quality of lesson 2.00 with poor criteria. Thus the quality of learning from before the action until after the action mendimi process improvement, so that cooperative learning model can be applied in class / semester 1 pgsd stkip pgri bangkalan.